1997
DOI: 10.1093/ndt/12.7.1425
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of haemolytic-uraemic syndrome in renal transplants: a single-centre report

Abstract: Based upon these data and a review of the literature, it can be concluded that the risk of recurrence of HUS in the allograft is confined almost entirely to patients with atypical forms of HUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 1 publication
0
49
1
2
Order By: Relevance
“…Renal transplantation is not necessarily an option for non-Stx-HUS, at variance with Stx-HUS. Actually, approximately 50% of the patients who had a renal transplant had a recurrence of the disease in the grafted organ (86,155). Recurrences occur at a median time of 30 d after transplant (range, 0 d to 16 yr).…”
Section: Which Treatment For Non-stx-hus?mentioning
confidence: 99%
“…Renal transplantation is not necessarily an option for non-Stx-HUS, at variance with Stx-HUS. Actually, approximately 50% of the patients who had a renal transplant had a recurrence of the disease in the grafted organ (86,155). Recurrences occur at a median time of 30 d after transplant (range, 0 d to 16 yr).…”
Section: Which Treatment For Non-stx-hus?mentioning
confidence: 99%
“…ndividuals who suffer ESRD due to atypical hemolytic uremic syndrome (aHUS) have poor outcomes after kidney transplant because of high rates of disease recurrence (1)(2)(3). In the case of carriers of a CFH [complement factor H (CFH)] mutation, the recurrence risk is over 80%, usually accompanied by graft loss (2,4,5).…”
mentioning
confidence: 99%
“…Some authors have also emphasized that the risk of recurrence is higher in patients with recurrent and familial forms of HUS, whereas it would be negligible in children with the typical form of HUS. Miller et al (138) reported a recurrence rate of 67% among 18 patients with atypical HUS and of 17% among 6 patients with typical, diarrheaassociated HUS. The outcome of post-transplant HUS is poor, with a 5-yr graft failure rate of 63% in one series (139).…”
Section: Transplant-associated Thrombotic Microangiopathymentioning
confidence: 99%